Application of Flexural Timber Reinforcement in Light Concrete Beam Structure - Mohammad Amirulkhairi, Zubir; Nurul Jannah, Mohamad (Trans Tech Publication, 2014)
Timber is a capable alternative for reinforcement in concrete beam because it possesses high strength ratio compare to its weight although its strength is incompatible to steel. This study was conducted to highlight the flexural behaviour of beam reinforced with two types of timber; Balau and Meranti. Comparisons of behaviour have been made between samples applying the Reinforced Concrete Design to EC2. The result of flexural test shows that steel reinforcement beam (SRB) carried the utmost loads compared to timber sample beam which reinforced with Balau (BRB) and Meranti (MRB). Compared to the flexural strength of SRB, BRB reached about 69 % of the value while MRB reached to 66 % respectively. It was found that the failure mode of the timber beam was closely related to the load-deflection behaviour same as conventional steel beam. The larger the load-deflection value, the wider the range of cracking occurred.